2016
DOI: 10.1080/13854046.2016.1267803
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating cognitive screening and cognitive testing from neuropsychological assessment: implications for professional practice

Abstract: There is a growing awareness of the importance of cognitive health and disability, and of the importance of measurement of cognitive functions across the lifespan. For example, cognitive screening has been mandated by the Patient Protection and Affordable Care Act of 2010, and language contained within new psychiatric diagnostic criteria and healthcare regulatory changes reflect increased consideration of the importance of measurement of cognition. Changes such as these necessitate greater clarity on this impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 33 publications
0
32
0
2
Order By: Relevance
“…For example, studies of MCI have provided inconsistent support for a relationship between subjective cognitive complaints and objective neuropsychological performance and some have suggested that incorporating self-reported cognitive complaints into diagnostic criteria may confound impressions and result in diagnostic errors [5,14,15]. Additionally, while cognitive screening measures may be helpful for identifying individuals who may benefit from more comprehensive evaluation, they are limited in their diagnostic utility [16][17][18]. Moreover, relying on a single neuropsychological test score to render diagnostic decisions is likely to result in inaccurate diagnoses both due to the heterogeneity of MCI and dementia profiles [1,4,6,[19][20][21] as well as base rates for low test scores and test variability in older adults [22].…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies of MCI have provided inconsistent support for a relationship between subjective cognitive complaints and objective neuropsychological performance and some have suggested that incorporating self-reported cognitive complaints into diagnostic criteria may confound impressions and result in diagnostic errors [5,14,15]. Additionally, while cognitive screening measures may be helpful for identifying individuals who may benefit from more comprehensive evaluation, they are limited in their diagnostic utility [16][17][18]. Moreover, relying on a single neuropsychological test score to render diagnostic decisions is likely to result in inaccurate diagnoses both due to the heterogeneity of MCI and dementia profiles [1,4,6,[19][20][21] as well as base rates for low test scores and test variability in older adults [22].…”
Section: Introductionmentioning
confidence: 99%
“…When there is ample evidence for concern, a more comprehensive neuropsychological assessment is appropriate, given that cognitive screening measurement strategies are limited by generally low sensitivity and specificity rates, whereas gold standard neuropsychological test batteries are more sensitive and specific. [42][43][44] Measurement of cognitive health assessments for patients aged 65 and over was chosen for both scientific reasons and practical reasons. Assessing cognitive health status is appropriate in patients with neurologic illness at any age; an assessment of mental status is an important part of any comprehensive neurologic examination.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to screening, comprehensive assessment involves additional testing, gathering of collateral information, and analysis. 8 For example, primary prevention strategies to mitigate cardiac, vascular, and cerebrovascular events include conducting screening tests. Clinical wisdom, informed by evidence-based practice guidelines, guides expert interpretation of these findings, including triggers to gather comprehensive assessment.…”
Section: The Rationale Of Prospective Screening Of Medical Staffmentioning
confidence: 99%